Produksi Benih Ikan Kakap Putih Berkualitas Untuk Meningkatkan Ekonomi UMKM - Petrus Paulus Letsoin; Irwan Ismail; Moses Tjoanda; Jane Lulinda Dangeubun; Ongen R. Lekirupy (Lembaga Penjaminan Mutu Universitas Abdurachman Saleh Situbondo, 2025)
Barramundi (Lates calcarifer) is a highly potential aquaculture commodity in Indonesia. However, UMKM Alstonia currently faces significant challenges, particularly in the production of fry and fish feed. One of the main issues is the high cost of feed, which limits the quality and quantity of feeding. As a result, the fish receive poor nutrition, making them more susceptible to diseases and leading to high mortality rates during the rearing period up to harvest. Therefore, increasing the production of high-quality feed is crucial to support successful aquaculture and drive the economic growth of fishery-based MSMEs. Quality feed enhances productivity, business efficiency, and the competitiveness of fish farmers. Strengthening the capacity of UMKM Alstonia through training in feed formulation and larval rearing becomes essential. This initiative also serves as a practical learning platform for students to engage directly with the community, promoting technology transfer and skill development in aquaculture practices.